Nitidulidae (Coleoptera) from the Paleocene of Menat (France) - Kirejtshuk, Alexander G.; Nel, Andre (Zootaxa, 2018)
This paper is devoted to the study of the first Palaeocene Nitidulidae, all from the lacustrine outcrop of Menat (France), viz. Nitoraeopsis mixta gen. et sp. nov. (Epuraeinae, first fossil member of Taenioncini); ?Soronia spp. (S. menatensis sp. nov. and S. sp.) of the Soronia-complex of genera (Nitidulinae, Nitidulini); Menatoraea gen. nov. (M. typica sp. nov. (type species), M. angustitibialis sp. nov., M. laticollis sp. nov., and M. gracilis sp. nov.) of the Pocadius- or Thalycra-complexes, and Palaeolycra palaeocenica gen. et sp. nov. of the Thalycra-complex (Nitidulinae, Nitidulini); and ?Cryptarcha subglobosa sp. nov., oldest fossil record of the tribe Cryptarchini sensu stricto (Cryptarchinae). A key to the species of Menatoraea gen. nov. and a review of the fossil record of the family Nitidulidae are provided.